Recurrent Abdominal Pain: A Rare Presentation of Childhood Intestinal Lymphoma in a Bangladeshi Child (Northern International Medical College Journal, 2020)
In children, primary malignant tumors of the gastrointestinal (GI) tract are rare and accounts less than 5% of all pediatric neoplasms.1 Non-Hodgkin’s lymphoma (NHL) remains the most common malignancy of the GI tract in children.2 Moreover small intestine (PLI) is very uncommon. They are different in anatomic distribution and histologic appearance compared to common patterns in adult cases. The disease is rare and having variable clinical presentation that delayed early detection when the possibility of cure exists. The common presentations of PLI are bowel obstruction and intussusception.3,4 NHL of the gastrointestinal tract usually arises in the submucosal lymphoid tissue of the ileocecal region, extendtransmuraly, and involve local mesenteric lymph nodes extensively, forming a bulky abdominal mass. NHL most frequently involved the ileocecal valve (35.8%), followed by the small bowel (31.3%), large bowel (19.4%) and multiple gastrointestinal involvements (13.4%).5 Here we present a case report to show the scenario of a patient suffering from NHL where diagnosis was delayed. The child was suffering from recurrent abdominal pain (RAP) and various treatment was offered but he could not improve. Finally, he was diagnosed as a case of primary non-Hodgkin's lymphoma of the small intestine (PLI). Though PLI is a very uncommon malignancy in childhood.Northern International Medical College Journal Vol. 11 No. 1 July 2019, Page 438-439